The giant protein titin regulates the length of the striated muscle thick filament - Tonino, Paola (Nat Commun, 2017)
The contractile machinery of heart and skeletal muscles has as an essential component the thick filament, comprised of the molecular motor myosin. The thick filament is of a precisely controlled length, defining thereby the force level that muscles generate and how this force varies with muscle length. It has been speculated that the mechanism by which thick filament length is controlled involves the giant protein titin, but no conclusive support for this hypothesis exists. Here we show that in a mouse model in which we deleted two of titin’s C-zone super-repeats, thick filament length is reduced in cardiac and skeletal muscles. In addition, functional studies reveal reduced force generation and a dilated cardiomyopathy (DCM) phenotype. Thus, regulation of thick filament length depends on titin and is critical for maintaining muscle health.